Pseudobarbus outeniqua sp. nov., a new redfin species (Teleostei, Cyprinidae) from the Cape Fold Ecoregion of South Africa - Fatah Zarei; Pedro H. N. Bragança; Paul H. Skelton; Albert Chakona (ZooKeys)
Previous DNA-based studies identified four genetic lineages within Pseudobarbus afer: (i) the Mandela lineage confined to the Sundays, Swartkops, and Baakens river systems, (ii) the Krom lineage endemic to the Krom River system, (iii) the St Francis lineage occurring in the Gamtoos and adjacent river systems, and (iv) the Forest lineage occurring in several southern coastal river systems from the Tsitsikamma to the Klein Brak river system. Subsequent detailed morphological evaluation provided a redescription of P. afer s.s. (Mandela lineage), supported revalidation of P. senticeps (Krom lineage) and description of a new species, P. swartzi (St Francis lineage). The present study builds on these earlier findings and provides a formal description of the Forest lineage as a new species for science, Pseudobarbus outeniqua sp. nov. The new species differs from the aforementioned congeners by the conspicuous pigmentation on the centre of the scales which gives it a distinctive speckled hen pattern. The new species thus closely resembles the small-scale redfin, P. asper, in colour pattern, but it is readily separated from this species by genetic characters and fewer number of scales in predorsal region (16–17, mode 16 vs 18–26, mode 20–23) and around the caudal peduncle (14–15, mode 15 vs 16–22, mode 18–20). A revised key for the single-barbeled redfins is presented.